In vivo Detection of Cortical Microinfarcts on Ultrahigh‐Field MRI. Issue 1 (18th May 2012) - Ii, Yuichiro; Maeda, Masayuki; Kida, Hirotaka; Matsuo, Ko; Shindo, Akihiro; Taniguchi, Akira; Tomimoto, Hidekazu
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND AND PURPOSE Cortical microinfarcts (CMIs) are detected as small foci restricted to the cerebral cortex in autopsy brains. CMIs are thought to be caused by cerebral amyloid angiopathy (CAA) in the elderly and may be a risk for dementia. We aimed to visualize CMIs, which remain invisible on conventional MRI, using double inversion recovery (DIR) and 3‐dimensional fluid attenuated inversion recovery (3D‐FLAIR) on 3‐Tesla MRI. METHODS We prospectively performed DIR and 3D‐FLAIR images in 70 subjects with Alzheimer disease (AD; n = 47), mild cognitive impairment (n = 14), AD with cerebrovascular disease (CVD; n = 3), vascular dementia (VaD; n = 2), CAA‐associated intracerebral hemorrhage (ICH; n = 2) and one each of normal pressure hydrocephalus and dementia with Lewy bodies (DLB). Susceptibility‐weighted imaging (SWI) was performed to detect cerebral microbleeds (CMBs). RESULTS Nine subjects (five of AD and one each of AD with CVD, ICH, VaD, and DLB) had small intracortical high signal lesions on both DIR and 3D‐FLAIR images. All the nine subjects accompanied multiple lobar CMBs. These intracortical lesions were located in close proximity to CMBs, and were suggested to be CMIs. CONCLUSIONS DIR and 3D‐FLAIR images may open a way to visualize CMIs.